A patient with concurrent EBV-negative diffuse large B-cell lymphoma and angioimmunoblastic T-cell lymphoma: a case report - Satoskar, Monika A.; Lordo, Matthew R.; Jones, Daniel M.; Nowacki, Nicholas B.; Brammer, Jonathan E.; Reneau, John C.; Voorhees, Timothy J. (Frontiers in Hematology, 2024)
IntroductionDiffuse large B-cell lymphoma (DLBCL) is an aggressive form of non-Hodgkin lymphoma that accounts for approximately a quarter of all lymphomas in the United States. It is rare to have co-occurring T cell lymphoma with DLBCL as they often develop following treatment of DLBCL rather than concomitantly.Case presentationWe report a 71-year-old male patient diagnosed with Epstein–Barr virus (EBV) -negative DLBCL with concurrent angioimmunoblastic T-cell lymphoma (AITL). A right inguinal lymph node biopsy demonstrated aggressive B-cell lymphoma consistent with DLBCL with the non-germinal center immunophenotype that was EBV-negative. Furthermore, abnormal T-cells with irregular nuclear contours were found in T cell receptor sequencing with monoclonal gamma and beta T cells. A bone marrow biopsy demonstrated occasional large atypical CD3+PD1+ T cells with corresponding identical T-cell receptor clones in the lymph node biopsy. Next-generation sequencing from the lymph node biopsy demonstrated dual inactivating TET2 mutations.ConclusionComposite DLBCL and AITL is a rare occurrence and the absence of EBV is even more so. Given the rare nature of having these two hematologic malignancies simultaneously, no standard of care exists. However, R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) is a regimen commonly used in both malignancies individually, and therefore this patient was treated using this approach achieving a partial remission after four cycles of therapy. Unfortunately, he developed refractory disease 1 month after completion of six cycles of R-CHOP.